Pengaruh Digital Marketing Terhadap Brand Image dan Brand Awareness Teh Walini - Madasansa, Amienda Cahya; Trimo, Lucyana; Utami, Hesty Nurul; Fatimah, Sri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Tea (Camellia sinensis) is a commodity that is the mainstay of the plantation subsector. One of the tea brands managed by PT Perkebunan Nusantara I Regional 2 is Walini Tea. Walini Tea is a tea that has advantages over other brands, such as high quality tea, processed by itself, and has many flavors. In its marketing activities, Teh Walini utilizes digital marketing, especially through social media to introduce its products by expanding its market reach. The purpose of this research is to find out the characteristics of Teh Walini consumers and analyze how digital marketing (X) affects brand image (Y1) and brand awareness (Y2). Quantitative research with an online survey method to 200 consumers of Teh Walini who use social media is the approach in this research. In analyzing primary data, the method used in this research is SEM-PLS utilizing SmartPLS 4 software. The results obtained are the effect of digital marketing on brand image and brand awareness is positive and significant.